Borrowing to live : consumer and mortgage credit revisited - Retsinas, Nicolas Paul, 1946-; Belsky, Eric S. (James A. Johnson metro series., 2008)
"Dissects the current state of consumer and mortgage credit in the United States and helps point the way out of the current impasse"--Provided by publisher